COMPARATIVE COMPUTATIONAL CHARACTERIZATION OF FERRIC CYTOCHROME P450 AND SUPEROXIDE REDUCTASE BINDING TO CYANIDE - SILAGHI-DUMITRESCU, Radu; CIOLOBOC, Daniela (Studia Universitatis Babeș-Bolyai Chemia, 2016)
The active sites of the enzymes superoxide reductase (SOR) and cytochrome P450 feature square pyramidal FeN4S centers, with a thiolate in axial position trans to the substrate binding site but with differing equatorial nitrogenous ligands. The respective catalytic cycles also share a common intermediate – a ferric-(hydro)peroxo species. The detailed catalytic mechanisms are still a matter of debate for both enzymes, as some of their key catalytic intermediates have very short lifetimes. Inhibitors such as cyanide were therefore often employed to probe active sites of these enzymes and identify important structural features controlling reactivity; among these studies, ENDOR spectral data on ferric-cyanide complexes were previously reported. Here, density functional calculations are employed in order to more accurately correlate the experimental data with electronic structure elements. The data are shown to be in good agreement with experiment and also provide new insight.